Benefits of visual management in construction: cases from the transportation sector in England. Issue 2 (3rd April 2017) - Tezel, Algan; Aziz, Zeeshan
Abstract : Purpose: The purpose of this paper is to explore the benefits of visual management (VM) systems in transportation construction projects in England. Design/methodology/approach: Following a comprehensive literature review, the benefits of VM were investigated through action and case study research executed within two construction projects in England. Findings: The main findings are: VM can contribute to increased self-management, better team coordination, better promises or an increasing plan percent complete, easier control for the management and improved workplace conditions in the transportation sector. It is important for the management to obtain the engagement of their workforce for VM through increased participation and show the actual benefits. However, managerial monitoring and control on the systems should not be underestimated. Originality/value: The transportation sector in England has been systematically deploying Lean construction techniques in its operations for a while. One of those Lean techniques is a close-range visual communication strategy called VM. The literature on the VM implementation in construction is scarce and generally limited to the building construction context. This paper documents the benefits of VM systems for the transportation sector by using data captured through both qualitative and quantitative data collection methods. The paper also identifies a set of recommendations for similar research efforts in the transportation context in the future.